2019
DOI: 10.1038/s41598-019-56421-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptomic and functional immunological approach for assessing the invasiveness of bivalve alien species

Abstract: Biological invasions started when humans moved species beyond their normal geographic limits. Bivalves are the most notoriously invasive species in subtidal aquatic environments. Next-generation sequencing technologies are applied to understand the molecular mechanisms involved in the invasion. The ecological immunology focuses on the role of immunity in invasion, and its magnitude could help to predict the invasiveness of alien species. A remarkable case of invasion has been reported in the Ría de Vigo (Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Generally, granulocytes show higher phagocytosis capacities than hyalinocytes, which has been documented in oysters C. ariakensis (151) (113), M. unguiculatus (117), P. canaliculus (119), P. perna (120), P. viridis (122) and X. securis (124); and in freshwater mussels Amblema plicata, Quadrula quadrula (131), D. chilensis (128), L. marginalis (140) and S. cumingii (145) and in the pearl oyster P. imbricata (175). There are also studies where no differences in immune responses between the haemocytes types were found, as it happened in the ark clam A. kagoshimensis (86).…”
Section: Phagocytosis and Encapsulationmentioning
confidence: 84%
See 1 more Smart Citation
“…Generally, granulocytes show higher phagocytosis capacities than hyalinocytes, which has been documented in oysters C. ariakensis (151) (113), M. unguiculatus (117), P. canaliculus (119), P. perna (120), P. viridis (122) and X. securis (124); and in freshwater mussels Amblema plicata, Quadrula quadrula (131), D. chilensis (128), L. marginalis (140) and S. cumingii (145) and in the pearl oyster P. imbricata (175). There are also studies where no differences in immune responses between the haemocytes types were found, as it happened in the ark clam A. kagoshimensis (86).…”
Section: Phagocytosis and Encapsulationmentioning
confidence: 84%
“…The production of radicals with microbicidal activity, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), is induced after phagocytosis and it may be used to evaluate the immunocompetence in different haemocyte subsets (156). Oxidative activity through ROS production is generally higher in granulocytes than in hyalinocytes, which was observed in oysters C. ariakensis (151), C. gigas (154,156,250,251), C. hongkongensis (157), C. nippona (160), C. virginica (167,252), O. chilensis (169), Hyotissa hyotis, Ostrea circumpicta, S. kegaki (148), and S. glomerata (173); in clams R. decussatus (73) and R. philippinarum (75); in the geoduck clam P. globosa (45); in ark clams A. broughtonii, A. kagoshimensis and T. granosa (82); in marine mussels M. galloprovincialis (114), M. unguiculatus (117), P. canaliculus (119), P. viridis (122), and X. securis (124); and in freshwater mussels L. marginalis (140). In L. marginalis, granulocytes were identified as the principal phagocytes with prominent activity of superoxide anion (a ROS) and nitric oxide (NO, a RNS) (140).…”
Section: Oxidative Activitymentioning
confidence: 99%
“…We detected four invasive species on the Galician coast, with the bivalve Xenostrobus securis being one of the most harmful invasive molluscs. The presence of X. securis on the Galician coast has been described ( 129 ), and its invasiveness and potential impact on autochthonous communities have already been evaluated ( 130 , 131 ). In contrast, the microscopic arthropod Pseudodiaptomus marinus has not been previously reported, and its high abundance could suggest the presence of a stable population of this species in northwestern Spain between the previously recorded distribution areas of northern Europe and Mediterranean Sea ( 132 ) using a comparable metabarcoding approach ( 133 ).…”
Section: Discussionmentioning
confidence: 99%
“…During initial colonization, physiological acclimation, phenotypic plasticity and epigenetic modification can buffer adverse environmental effects organisms are exposed to, and we could already show that tissuespecific microbiota can play a decisive role in the initial stages of translocation (Lokmer et al, 2016). On the molecular level these fast responses should also be reflected in gene regulation (i.e., on the transcriptomic level), and several studies investigated the transcriptomic responses of invaders between species (Wellband and Heath, 2017;Romero et al, 2019), between native and invaded regions (Guggisberg et al, 2013;Vogel et al, 2017) or between invasive populations (Feis et al, 2018). Yet, with only few exceptions (Parente et al, 2017) hardly any study actually tried to explicitly link transcriptomic and genomic differentiation in the same invasive species system.…”
Section: Introductionmentioning
confidence: 98%